2015
DOI: 10.1021/acs.jnatprod.5b00173
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Ca2+ Movement in the Involvement of Baicalein-Induced Cytotoxicity in ZR-75-1 Human Breast Cancer Cells

Abstract: Baicalein (5,6,7-trihydroxyflavone) (1) has been found to be active against a wide variety of cancer cells. However, the molecular mechanism underlying the effects of 1 on the induction of Ca(2+) movement and cytotoxicity in human breast cancer cells is unknown. This study examined the relationship between 1-induced Ca(2+) signaling and cytotoxicity in ZR-75-1 human breast cancer cells. The in vitro investigations reported herein produced the following results: (i) Compound 1 increased intracellular Ca(2+) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Curcumin increased Ca 2+ influx into cells, depolarized ∆Ψm, released Cytc, and activated caspases in human hepatocellular carcinoma cells [161]. Honokiol (5,3′-dially-2,4′-dihydroxybiphenyl), eugenol (4-ally-2-methoxyphenol), gallic acid, and baicalein caused phospholipase C-dependent Ca 2+ release from the endoplasmic reticulum (ER) and Ca 2+ influx into cells through the transient receptor potential channel melastatin 8, or PKC-dependent channel in human glioblastoma and breast cancer cells [162,163,164]. Morusin (an extended 5,2′,4′-trihydroxyflavone) induced cell death by VDAC-mediated Ca 2+ overload in epithelial ovarian cancer [165].…”
Section: Polyphenols Induce Cell Death In Cancer By Activation Of mentioning
confidence: 99%
“…Curcumin increased Ca 2+ influx into cells, depolarized ∆Ψm, released Cytc, and activated caspases in human hepatocellular carcinoma cells [161]. Honokiol (5,3′-dially-2,4′-dihydroxybiphenyl), eugenol (4-ally-2-methoxyphenol), gallic acid, and baicalein caused phospholipase C-dependent Ca 2+ release from the endoplasmic reticulum (ER) and Ca 2+ influx into cells through the transient receptor potential channel melastatin 8, or PKC-dependent channel in human glioblastoma and breast cancer cells [162,163,164]. Morusin (an extended 5,2′,4′-trihydroxyflavone) induced cell death by VDAC-mediated Ca 2+ overload in epithelial ovarian cancer [165].…”
Section: Polyphenols Induce Cell Death In Cancer By Activation Of mentioning
confidence: 99%
“…Moreover, the release of Ca 2+ from the ER to cytosol is dependent on the PLC pathway. 33 Increase in the free Ca 2+ concentrations always leads to aggravated ER stress and the disturbance of mitochondrial membrane potential, thus leading to mitochondrial apoptosis. 34 Hoyer-Hansen et al demonstrated that unwanted cytoplasmic Ca 2+ led to autophagy via the activation of CaM-dependent kinase kinase-β and inhibition of mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein (5,6,7-trihydroxyflavone) is the primary flavonoid derived from Scutellaria baicalensis Georgi, whose structure is composed of a three-ring flavone backbone with phenolic hydroxyl at the 5' , 6' , and 7' position. Several studies have revealed that baicalein possesses antitumor activity in breast cancer and exhibits anti-estrogenic activity (20)(21)(22). In our previous study, it was demonstrated that baicalein is able to suppress E2 enhanced migration, adhesion and invasion of breast cancer cells and interferes with E2 or G-1 induced GPR30 signaling activation (23).…”
Section: Introductionmentioning
confidence: 96%